PHYSICAL CHARACTERIZATION OF IBUPROFEN-STEARIC ACID BINARY MIXTURE DUE TO COMPRESSION FORCE - Setyawan, Dwi; Isadiartuti, Dewi; Betari, Sita Desti; Paramita, Diajeng Putri (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Aim of this research is to determine physical characteristic of ibuprofen-stearic acid due to compression force. Binary mixture of ibuprofen-stearic acid with weight ratio of 4:6, 5:5, and 6:4 was compressed under various compression force using hydraulic press with 13mm diameter flat punch.Identification of solid state interaction between these two components was performed by Hot Stage Microscopy (HSM). Physical characterization has been studied byDifferential Thermal Analysis (DTA), X-ray Powder Diffraction (XRPD), Scanning Electron Microscopy (SEM), and (Fourier Transform Infrared (FT-IR) spectroscopy. According to hardness measurement, 4:6 weight ratio has the highest tensile strength on 170.6N/cm2 under 19.93kN compression force. Interaction identification by HSM showed single blank line that indicates eutectic formation. Thermal analysis of DTA also revealed eutectic formation upon compression whichthe endotermic peak of ratio of 4:6has the lowest melting temperature of 53.2°C. X-ray diffraction of three peaksgenerally showed that peak intensity decreases as compression force increases, but at particular point it begins to increase again. Sintering phenomenon at the surface of compressed tablet was observed from SEM analysis. FT-IR study confirms the formation of simple eutectic. Key words: ibuprofen, stearic acid, binary mixture, compression force, physical characterization